People Don’t Choose to be Paid Less: the Pay Gap: Invited Editorial - Hotine, Emily (Journal of the Nuffield Department of Surgical Sciences, 2020)
The pay gap is a topic that has become increasingly examined in recent years. Yet there are still misconceptions surrounding what it is, what causes it and how it can be remedied. When these misconceptions are corrected, it often leads to claims that the pay gap is meaningless or that it isn’t a problem in the first place, so it doesn’t need to be fixed. These analyses of the pay gap tend to be reductive and lack nuance and understanding of the wider societal context of discrimination. Through looking at the data and the research within societal and cultural contexts, we can see that the pay gap is a complex problem with many contributing factors and, as a result, it requires intervention at governmental, cultural and individual levels.